Persepsi Siswa dan Guru Biologi SMAN 15 Pekanbaru terhadap Penilaian yang di Gunakan dalam Proses Pembelajaran - Rosa Hermalia; Nurkhairo Hidayati (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
Education in Indonesia is increasingly developing through a long journey of sustainable results and has been determined by the applicable curriculum through assessment results in the world of education generally covering cognitive aspects, namely how much students are able to remember and understand the subject matter. The aim of this research is to find out the results of the assessments used in the learning process at SMA Negeri 15 Pekanbaru. This research uses survey research with data collection techniques, namely questionnaires and interviews with teachers and students. The results of this research show that teachers' perceptions of assessment have received very good appreciation in learning.